Enhancing Path Delay Fault Coverage by Weighted Pseudorandom Test Generation - Øystein Gjermundnes; Einar J. Aas (ХНУРЭ, 2008)
The implementation of a system for analyzing circuits with respect to their path-delay fault testability is presented. It includes a path-delay fault simulator, and an ATPG for path-delay faults combined into a test tool. The test tool is used to evaluate the performance of several different test vector generators. The test generators exploit weighted pseudo-random stimuli generation, based on arithmetic BIST and SIC patterns. The main goal is to find efficient heuristics that improves path-delay fault detection efficiency in terms of test time. We show that weighted ABIST stimuli are productive for detecting the K-longest path-delay faults for most circuits. On the average, we obtained fault coverage of 92.6% for the 20.000 longest paths on iscas’85 circuits. Index Terms − Built-in testing, Fault diagnosis, Automatic testing.
Keywords: Automatic testing; Fault diagnosis; Built-in testing